1999
DOI: 10.1038/sj.bjc.6690609
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and perinatal risk factors for childhood leukaemia and other malignancies: a Scottish case control study

Abstract: The considerable burden of childhood cancer, in terms of both morbidity and mortality, has generated extensive aetiological research over recent decades. Despite these efforts, apart from ionizing radiation, the causes of childhood leukaemia and other malignancies remain largely unexplained (Doll, 1989). The identification of risk factors has frequently focused on the vulnerable period of intrauterine growth and development, birth and neonatal life. The population-based Scottish case control study of childhood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
167
3
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(193 citation statements)
references
References 29 publications
13
167
3
8
Order By: Relevance
“…Our finding of around a two-fold greater risk of childhood ALL among children born into surroundings where there is little overcrowding supports the hypothesis that childhood ALL is caused by an inappropriate immunological response to a common infection or infections in children whose immune systems are not 'programmed' by early exposure to these infections (Greaves and Alexander, 1993;Greaves, 1997). In support of this hypothesis, several studies have reported that early exposure to infection (van Steensel-Moll et al, 1986;Kaatsch et al, 1996;McKinney et al, 1999) is associated with a reduced risk of childhood ALL. However, contrary to what may be expected if this hypothesis is correct, we and several other investigators (Shaw et al, 1984;Shu et al, 1988;Kaye et al, 1991;McKinney et al, 1999;Schuz et al, 1999;Rosenbaum et al, 2000) did not find that later-born infants had a lower risk of ALL than first-born infants.…”
Section: Socioeconomic Status and Household Densitysupporting
confidence: 75%
See 4 more Smart Citations
“…Our finding of around a two-fold greater risk of childhood ALL among children born into surroundings where there is little overcrowding supports the hypothesis that childhood ALL is caused by an inappropriate immunological response to a common infection or infections in children whose immune systems are not 'programmed' by early exposure to these infections (Greaves and Alexander, 1993;Greaves, 1997). In support of this hypothesis, several studies have reported that early exposure to infection (van Steensel-Moll et al, 1986;Kaatsch et al, 1996;McKinney et al, 1999) is associated with a reduced risk of childhood ALL. However, contrary to what may be expected if this hypothesis is correct, we and several other investigators (Shaw et al, 1984;Shu et al, 1988;Kaye et al, 1991;McKinney et al, 1999;Schuz et al, 1999;Rosenbaum et al, 2000) did not find that later-born infants had a lower risk of ALL than first-born infants.…”
Section: Socioeconomic Status and Household Densitysupporting
confidence: 75%
“…Most previous reports failed to find an association between ALL and length of gestation (Kaye et al, 1991;Kaatsch et al, 1996;McKinney et al, 1999), although one study has shown a similar, but not statistically significant, relationship (Dockerty et al, 1999). Some studies have reported positive associations between history of previous foetal loss and childhood leukaemia (van Steensel-Moll et al, 1985;Kaye et al, 1991), others found no association (Schuz et al, 1999) while in the current study, as in a Chinese case -control study (Shu et al, 1988) an inverse association was found.…”
Section: Gestational Age and Previous History Of Miscarriagecontrasting
confidence: 51%
See 3 more Smart Citations